A meta-analysis of public attitudes toward ex-offenders - Rade, Candalyn B. (Criminal justice and behavior, 2016)
Ex-offenders face barriers to community reintegration including negative attitudes held by members of the public. This meta-analysis summarizes the extant research on the correlates of public attitudes toward ex-offenders?namely, public, ex-offender, and community characteristics?and the moderating effects of sexual offense history. A systematic search of four databases (PsycINFO, Web of Science, National Criminal Justice Reference Service [NCJRS], and ProQuest Dissertation & Theses) identified 19 records, consisting of 9,355 participants. Results revealed small associations between correlate variables and attitudes, suggesting that people are more similar than different in their attitudes toward ex-offenders. Indeed, only political ideology, interpersonal contact, and sexual offense history emerged as significant correlates. Moderation analyses revealed differences in public attitudes toward ex-offenders based upon the year a record was produced. Findings reveal the need for additional research examining moderators of public attitudes toward ex-offenders and suggest that interventions should explore ways to incorporate interpersonal contact and reduce stigma related to criminal histories.